2016
DOI: 10.1002/ajim.22674
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary abnormalities as a result of exposure to Libby amphibole during childhood and adolescence—The Pre‐Adult Latency Study (PALS)

Abstract: Cumulative environmental exposure was associated with risk of pleural thickening. Among this cohort, quantitative measures of pleural thickening were associated with decreased PFT. Am. J. Ind. Med. 60:20-34, 2017. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 55 publications
0
24
0
Order By: Relevance
“…Symptoms included severe (prolonged) fatigue, Raynaud's phenomenon, rashes, swollen painful joints, and musculoskeletal pain. Although many of the patients also suffer from pulmonary abnormalities indicative of ARD, it is generally not interstitial disease (Antao et al 2012;Peipins, et al 2003), but rather a thin lamellar pleural thickening (Black, et al 2014;Szeinuk, et al 2017). The purpose of this case series was to describe a small sample of people who presented with asbestos-related diseases and autoimmune disease.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Symptoms included severe (prolonged) fatigue, Raynaud's phenomenon, rashes, swollen painful joints, and musculoskeletal pain. Although many of the patients also suffer from pulmonary abnormalities indicative of ARD, it is generally not interstitial disease (Antao et al 2012;Peipins, et al 2003), but rather a thin lamellar pleural thickening (Black, et al 2014;Szeinuk, et al 2017). The purpose of this case series was to describe a small sample of people who presented with asbestos-related diseases and autoimmune disease.…”
Section: Discussionmentioning
confidence: 99%
“…Various investigators reported that this uncertainty is based upon the possibility that not all forms of asbestos drive an autoimmune response, and that autoimmune responses are seen more often with amphibole, rather than chrysotile, exposures (Ferro, et al 2013;Pfau, et al 2015;Pfau 2017). Historically, chrysotile exposures have been prevalent due to extensive commercial use, but reductions in asbestos mining and product manufacturing are revealing that environmental asbestos exposures are abundant, often contain amphibole fibers, and exert adverse health impacts even at low levels of exposure (Baumann et al 2013;Wolfe, et al 2017;Bayram and Bakan 2014, Buck, et al 2013, Lockey, et al 2015, Andujar et al, 2016Lemen, 2016;Szeinuk, et al 2017). Therefore, the current study regarding LAA suggests that more research is needed regarding specific mineral fibers that may be triggers for SAID.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Mediastinal calcified circumscribed thickening was also present. No lamellar pleural thickening was observed . One underwent surgical pleural biopsy due to suspicion of malignant mesothelioma (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…For example, the mine waste material was used on the school running track, the community baseball field and in many residential gardens as a soil amendment (6). Screening studies have identified associations between nonoccupational, environmental exposures to these materials and occurrence of pleural abnormalities (27,28). Despite the small size of the community, elevated SMRs for respiratory cancers have been observed (29), and 11 mesothelioma case reports among non-occupationally exposed residents were described (30).…”
Section: Environmental Exposure From Industrial Operationsmentioning
confidence: 99%